Pengaruh Knowledge Management Dan Budaya Organisasi Terhadap Kinerja Karyawan Melalui Kepuasan Kerja Sebagai Variabel Intervening Pada Karyawan PT. Aura Mandiri Sejahtera Kecamatan Tigo Nagari Kabupaten Pasaman - Dewina Putri; Dori Mittra Candana; Hilda Mary (Jurnal Ekonomi dan Bisnis Digital, 2026)
This study aims to analyze the effect of knowledge management and organizational culture on employee performance through job satisfaction as an intervening variable. The research used a quantitative approach with a sample of 70 employees. Data were collected through Likert-scale questionnaires and analyzed using Structural Equation Modeling based on Partial Least Squares (SEM-PLS) with SmartPLS software. The results show that knowledge management and organizational culture have a positive and significant effect on job satisfaction. Organizational culture and job satisfaction have a positive and significant effect on employee performance, while knowledge management does not have a significant direct effect on performance. Mediation testing confirms that job satisfaction mediates the relationship between knowledge management and organizational culture on employee performance. These findings indicate that improving employee performance is more effective when supported by strong knowledge management practices and organizational culture that enhance job satisfaction.